Extreme municipal fiscal stress and austerity? A case study of fiscal reform after Chapter 9 bankruptcy. (May 2020) - Davidson, Mark
Post-recession urban restructuring in the U.S. has involved national and state governments pushing budget problems to the local level, with municipalities implementing a variety of responsive reforms. Although the term "austerity" has often been used to characterize these reforms, others have argued municipal responses to fiscal stress have been largely "pragmatic". Disagreement therefore exists about the extent to which austerity is a post-recession tendency across U.S. urban governance. However, there is a consensus that extreme municipal fiscal stress is linked to austerity restructuring. But can cities who have experienced extreme fiscal stress avoid austerity restructuring? This paper draws on research that examined bankruptcy-related reform in the City of Vallejo, California. In 2008, Vallejo became the first municipality to file for Chapter 9 bankruptcy after the financial crisis. During and after its bankruptcy, the City has faced extreme budget problems, making it a prime candidate for austerity restructuring. However, research shows that Vallejo undertook a set of post-bankruptcy reforms—controlling labor costs, revenue raising, managing risk, participatory budgeting—that are not collectively characteristic of austerity or pragmatism. In conclusion, the paper reflects on the political and ideological factors that shaped Vallejo's post-recession restructuring and how the City's core fiscal problems have avoided resolution.